(untitled) (Media Kesehatan Masyarakat Indonesia, 2019)
Since the enactment of the National Health Insurance (JKN) policy, all Primary Health Care in Indonesia must follow accreditation. Through accreditation, it is expected that the quality of Primary Health Care services will increase, one of which can be seen from the increase in patient satisfaction. This study was conducted to analyze the effect of accreditation on patient satisfaction. The study was conducted on 90 Primary Health Care patients who had visited the Primary Health Care before and after accreditation. Data retrieval has been done crossectionally. The paired-sample T test was conducted to see the significance of differences in satisfaction scores before and after accreditation. The results showed that there were significant differences in satisfaction scores between before and after accreditation for the dimensions of responsiveness, credibility, competence, communication, security, access, courtesy, understanding customer and tangibles. In the reliability dimension no significant differences were found. While specifically for the cutomer understanding dimension there was a decrease in satisfaction scores after accreditation. Therefore, it is important for Primary Health Care to improve their service systems, especially related to fulfilling service promises that have been set as quality objectives. Dissemination of information to the public must be improved, so that the public becomes aware of the existence of programs run by the Primary Health Care, such as accreditation.